School‐based brief psycho‐educational intervention to raise adolescent cancer awareness and address barriers to medical help‐seeking about cancer: a cluster randomised controlled trial. Issue 7 (27th October 2015) - Hubbard, Gill; Stoddart, Iona; Forbat, Liz; Neal, Richard D.; O'Carroll, Ronan E.; Haw, Sally; Rauchhaus, Petra; Kyle, Richard G.
Abstract: Objectives: Raising cancer awareness and addressing barriers to help‐seeking may improve early diagnosis. The aim was to assess whether a psycho‐educational intervention increased adolescents' cancer awareness and addressed help‐seeking barriers. Methods: This was a cluster randomised controlled trial involving 2173 adolescents in 20 schools. The intervention was a 50‐min presentation delivered by a member of Teenage Cancer Trust's (UK charity) education team. Schools were stratified by deprivation and roll size and randomly allocated to intervention/control conditions within these strata. Outcome measures were the number of cancer warning signs and cancer risk factors recognised, help‐seeking barriers endorsed and cancer communication. Communication self‐efficacy and intervention fidelity were also assessed. Results: Regression models showed significant differences in the number of cancer warning signs and risk factors recognised between intervention and control groups. In intervention schools, the greatest increases in recognition of cancer warning signs at 6‐month follow‐up were for unexplained weight loss (from 44.2% to 62.0%) and change in the appearance of a mole (from 46.3% to 70.7%), up by 17.8% and 24.4%, respectively. Greatest increases in recognition of cancer risk factors were for getting sunburnt more than once as a child (from 41.0% to 57.6%) and being overweight (from 42.7% to 55.5%), up by 16.6% and 12.8%, respectively. Regression models showed that adolescents in intervention schools were 2.7 times more likely to discuss cancer at 2‐week follow‐up compared with the control group. No differences in endorsement of barriers to help‐seeking were observed. Conclusions: School‐based brief psycho‐educational interventions are easy to deliver, require little resource and improve cancer awareness. © 2015 The Authors. Psycho‐Oncology published by John Wiley & Sons Ltd.